2015
DOI: 10.5539/gjhs.v8n3p26
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Intelligence Quotient (IQ)among 3 to 7-year-old strabismic and nonstrabismic children in an Iranian population

Abstract: This study was designed to compare the Intelligence Quotient (IQ) among 3 to 7-year-old strabismic and nonstrabismic children in an Iranian population.In this cross-sectional study, 108 preschool children with equal numbers of strabismic/non-strabismic disorder (age 3–7 years) were randomly selected from exceptional strabismus clinics of Ahvaz and were evaluated with the preschool and primary scale of intelligence versions of Wechsler (WPPSI).In the current study, 108 children were evaluated. In strabismic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In this study, XT patients had higher IQ scores than X(T) patients, which is consistent with previous studies [17,18]. It has been shown that most XT patients are deteriorated from X(T) [36], and XT may present decompensated X(T) [37], indicating that XT and X(T) have the same etiological basis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, XT patients had higher IQ scores than X(T) patients, which is consistent with previous studies [17,18]. It has been shown that most XT patients are deteriorated from X(T) [36], and XT may present decompensated X(T) [37], indicating that XT and X(T) have the same etiological basis.…”
Section: Discussionsupporting
confidence: 92%
“…In a study of the Iranian population, Bagheri et al have reported that patients with congenital strabismus (mean age = 18.4 ± 10.5 years, range: 4–63) had a lower mean intelligence quotient (IQ) score than the normal population [17]. By contrast, Ghaderpanah et al adopted WPPSI (the preschool and primary scale of intelligence versions of Wechsler) test to evaluate 3 to 7-year-old strabismus Iranian children, and found that there was no difference in the verbal intelligence quotient, operational intelligence quotient, and total intelligence quotient between strabismus children and normal children, and no negative effect of strabismus on preschool children’s intelligence quotient was found [18]. Thus, the effect of strabismus on intelligence remains controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the mechanism of the link between these two phenomena is not clearly understood and is confounded by a number of factors, there is evidence to suggest that both environmental and genetic factors may contribute to this relationship (26). In a study which done with 3 to 7-year-old Strabismic and Nonstrabismic Children in an Iranian Population, did not found a significant negative interference of strabismus on IQ score of preschool children (27). Considering all these studies, there seems to be a common genetic basis of between intelligence and myopia, in this respect, further studies on genetic regions are needed.…”
Section: Discussionmentioning
confidence: 99%